Enzyme-catalyzed amine-functionalization of poly(ethylene-glycol) - Judit Eva Puskas; Enikő Krisch; Aswathy Sasidharan Pillai; Prajakatta Mulay (eXPRESS Polymer Letters)
This paper presents a new method for the amine-functionalization of poly(ethylene glycol) (PEG) of Mn =2050 g/mol via Candida antarctica lipase B (CALB)-catalyzed esterification of tert-butyloxycarbonyl (tBOC)-protected β-Alanine and L-Alanine. NMR showed full conversion for protected β-Alanine, and MALDI-ToF demonstrated the purity of the product. After deprotection, the desired diamine-functionalized PEG was obtained. Protected L-Alanine did not reach full conversion by NMR, likely due to the steric hindrance of its methyl side group.